Dance Matters in Ireland Contemporary Dance Performance and Practice (Springer International Publishing, 2018)
This book addresses the need for critical scholarship about contemporary dance practices in Ireland. Bringing together key voices from a new wave of scholarship to examine recent practice and research in the field of contemporary dance, it examines the excitingly diverse range of choreographers and works that are transforming Ireland's performance landscape. The first section provides a chronologically-ordered collection of critical essays to ground the reader in some of the most important issues currently at play in contemporary dance in Ireland. The second section then provides an interrogation of individual choreographers' processes. The book traces new choreographic work and trends through a broad array of topics, including somatics in performance, screendance, cultural trauma, dance archives, affect studies, feminist perspectives, choreographic process, the dancer's voice, interdisciplinarity, and pedagogical paradigms.